Von Willebrand factor: A key glycoprotein involved in thrombo-inflammatory complications of COVID-19 - Choudhary Shalki; Sharma Kajal; Singh Pankaj Kumar (Elsevier Ireland Ltd, 2022)
COVID-19 is an ongoing public health emergency that has affected millions of people worldwide and is still a threat to many more. One of the pathophysiological features of COVID-19 is associated with the activation of vascular endothelial cells (ECs) leading to the disruption of vascular integrity, coagulation and inflammation. An interlink mechanism between coagulation and inflammatory pathways has been reported in COVID-19. Multiple components are involved in these pathological pathways. Out of all, Von Willebrand Factor (VWF) is one of the primary components of coagulation pathway and also a mediator of vascular inflammation that plays an important role in thrombo-inflammation that further leads to acute respiratory distress syndrome (ARDS). The thrombo-inflammatory co-morbidities such as hyper-coagulation, thrombosis, ARDS etc. have become the major cause of mortality in the patients of COVID-19 admitted to the ICU. Thus, VWF can be explored as a potential target to manage COVID-19 associated co-morbidities. Supporting this hypothesis, there are literature reports which disclose previous attempts to target VWF for the management of thrombo-inflammation in other pathological conditions. The current report summarizes emerging insights into the pathophysiology, mechanism(s), diagnosis, management and foundations for research on this less explored clinically relevant glycoprotein as coagulation biomarker in COVID-19.